THE INFLUENCE OF COMPETENCE, WORK MOTIVATION AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE IN THE MILLENNIAL GENERATION IN THE DKI JAKARTA REGION - Muhammad Iqbal Prasetio; Hasanah Hasanah (Jurnal Ekonomi Trisakti, 2022)
Employee performance in the Millennial Generation in the DKI Jakarta Region is experiencing problems. Problems in this performance are associated with several constructs such as competence, work motivation, career development and organizational commitment of DKI Jakarta Millennial Employees. The purpose of this study was to determine the significance of the effect of competence, work motivation and career development on employee performance, with organizational commitment as a moderating variable in the Millennial Generation in the DKI Jakarta Region. Research data obtained from the distribution of questionnaires, which will then be processed through data processing methods with SPSS version 23.0. The sample in this study amounted to 245 people using the proportional stratified random sampling method. The results of the study stated that 1) Competence had a positive and significant effect on organizational commitment, 2) Work Motivation had a positive and significant effect on organizational commitment, 3) Career Development had a positive and significant effect on organizational commitment, 4) Competence had a positive and significant effect on performance, 5 ) Work motivation has a positive and significant effect on performance, 6) Career development has no and no significant effect on performance, 7) Organizational Commitment has a positive and significant effect on performance.